PENGARUH MOTIVASI, KEPEMIMPINAN, KOMUNIKASI DAN STRES KERJA TERHADAP KINERJA DAN PENGEMBANGAN KARIER PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PANGKALPINANG - Intan Permata; Wardati Arfani (JEM Jurnal Ekonomi dan Manajemen, 2022)
This study aims to determine and analyze the effect of motivation, leadership, communication, and job stress on employee performance and career development. This research uses the descriptive-quantitative method. The population in this study were all employees at the Department of Population and Civil Registry of Pangkalpinang City, amounting to 54 respondents. Sampling technique using the census. Based on the results of the study, it was concluded that there was a significant effect of the variables of motivation, leadership, communication, and work stress on employee performance and career development. The results of the study also concluded that the influence of motivation, leadership, communication, and work stress variables partially on employee performance, where the communication variable has the greatest influence compared to other variables that affect employee performance.